Azizan: We'll consider quit rent rebate for UUM - News Straits, Times (New Straits Times, 2011)
ALOR STAR - The Pas-led Kedah government has denied claims that the quit rent for Universiti Utara Malaysia (UUM) has been increased to more than RM1 million since it took over the state administration three years ago.